Public Expenditure and Private Profit: Budgetary Decision in the British Empire, 1860-1912 - Davis, Lance E.; Huttenback, Robert A. (American Economic Review, 1977)
To imperial enthusiasts, Empire connoted the triumph of British principles over the powers of darkness and was a source of incalculable psychic and financial reward. The critics, however, saw an increasing burden on the British domestic taxpayer, while British subjects in the colonies contributed virtually nothing. Any analysis of the cost of empire in the context of nineteenth-century Britain must in large part rest on an understanding of the institutional mechanism that might have provided the base either for exploitation or selfless regeneration of barbarous places. In an earlier period, monopolies enforced by the military power of the state provided one such institutional structure. Later similar transfers might have been effected through the assertion of ownership over valuable resources in relatively fixed supply. However, even if British entrepreneurs had been omniscient enough to recognize such resources before their competitors, the profit opportunities must have been relatively limited. By 1860 Britain was committed to free trade and the Empire was as a consequence theoretically open to all. Thus, possibilities for direct monopolistic profits were very small; and similar competitive forces acted to reduce monopsonistic rents. Given such an environment, any exploitation must have rested on a set of government policies that thwarted competition and gave some shadowy imperialist an edge over his colonial, foreign and even domestic rivals. Thus the degree to which empire was exploitative as opposed to burdensome cannot be determined without reference to the government sector-and that appraisal is the focus of this paper. Every government policy involves a budgetary dual. Wars cannot be fought without armies being paid; tariffs can't protect local enterprise without some expenditure on enforcement, and even property rights cannot be guaranteed unless funds are devoted to legal and judicial needs. Of course, budgets are not always what they seem, but in the nineteenth and early twentieth centuries they did in large measure reflect the policies of government.